Better understanding of solar water evaporation systems using a biosourced foam and its modelling. (September 2022) - Fillet, R.; Nicolas, V.; Celzard, A.; Fierro, V.
Highlights: A water evaporation model is validated using a tannin foam. Material's light absorption, water diffusion and thickness are modelled. Insufficient water transport to the surface decreases evaporation by 40%. Insulating the exterior wall increases evaporation by 4%. Hot and dry climates have the highest water evaporation potential. Abstract: A two-dimensional axisymmetric finite element model of a solar evaporator based on a tannin foam has been developed using COMSOL Multiphysics. This model includes a set of boundary conditions and mass transfer within the porous structure. Experiments were conducted to validate the model as the parameters changed over time. Using the model, the effects of light absorption at the surface, water diffusion inside the material, and the thickness of the material and the insulating wall were investigated. We showed that a 38% decrease in evaporation rate was observed when water diffusion does not allow sufficient transport of water to the surface. In addition, an increase in light absorption from 0.8 to 0.9 increases the evaporation performance by 12% and insulation of the exterior does not yield significant changes. A final section of the article focuses on the temporal evolution of water evaporation in several locations around the world. We concluded that hot and dry climates have the highest evaporation potential. Among the cities studied, the highest theoretical evaporation for this biosourced foam was predicted for Dubai, 5342 kg·m −2, followed by Cairo, 4723 kg·m −2 .